Construção de um protótipo para um projeto piloto de correio pneumático para instituição financeira - RIBEIRO, Michel Ailis Farias (2022)
Transport via the pneumatic tube or also called pneumatic mail is a system that allows you to quickly and safely transport objects such as paper money, coins, documents, among others. The objects are placed inside capsules for their transport through one or more lines of tube. The capsule is driven by a pressure or suction of air. To send and receive these capsules there are several stations of different types, one for each application. Objects can be transported in hospitals, supermarkets, industries, gas stations, etc. In this work, a prototype was developed for a pilot project of a financial institution of the state of Pará, with the purpose of transporting cash (cash, coins and deposit envelopes), during construction, the viability of this type of transport was verified, and at the end the prototype was tested and validated so that its results were described through a technical sheet, from these results, possible improvements were exposed at the end of the work.